2006
DOI: 10.1158/1055-9965.epi-06-0592
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking and Survival after Ovarian Cancer Diagnosis

Abstract: We have examined the association between cigarette smoking and ovarian cancer survival in 676 women with invasive epithelial ovarian cancer, recruited into a casecontrol study in the early 1990s. Information about cigarette smoking and other personal and reproductive factors was obtained from a personal interview at the time of diagnosis. Cox proportional hazards models were used to evaluate the association between cigarette smoking and time to ovarian cancer death. Current smokers at diagnosis were more likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 22 publications
(23 reference statements)
5
22
1
Order By: Relevance
“…However, there was no distinction made between tumors of differing grades or histologies. Other studies have suggested that current cigarette use at the time of ovarian cancer diagnosis increases the risk of death by as much as 65% 10, 11 . While these investigations do adjust for such variables as tumor histology, stage, chemotherapy, and grade, the grading systems do not follow the two-tier system or FIGO grading criteria, thus making these conclusions difficult to interpret.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no distinction made between tumors of differing grades or histologies. Other studies have suggested that current cigarette use at the time of ovarian cancer diagnosis increases the risk of death by as much as 65% 10, 11 . While these investigations do adjust for such variables as tumor histology, stage, chemotherapy, and grade, the grading systems do not follow the two-tier system or FIGO grading criteria, thus making these conclusions difficult to interpret.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking status was defined as non-smoker, ex-smoker and current smoker. A regular smoker was defined as one who smokes at least 1 cigarette per day for over 1 year and a current smoker as one who regularly smokes for at least 1 year and continues to smoke within 1 year prior to surgery, an ex-smoker was defined as one who quit smoking for more than 1 year before surgery [17], [24]. Postoperative smoker was defined as one who smokes within first year postoperatively for at least one year or till death.…”
Section: Methodsmentioning
confidence: 99%
“…In the MALOVA study (n = 295 cases, 245 deaths) and an Australian study (676 cases, 419 deaths), women who reported smoking at the time of or within one year of diagnosis were at higher risk of dying (HR = 1.65, 95% CI = 1.22-2.24 and HR = 1.36, 05% CI = 1.01-1.84, respectively) [62,63]. However, in a Swedish study (635 cases, 396 deaths), there was no association with current smoking (HR = 0.94, 95% CI = 0.70-1.26) [34].…”
Section: Smokingmentioning
confidence: 99%